O fortalecimento da democracia partidária e o individualismo das candidaturas independentes - Igor Bruno Silva de Oliveira (2021)
Brazil has gone through moments of instability in its republican political history, with the Constitution of the Republic of 1988 having party democracy as a form of political representation. Thus, it mirrors the theory of political parties, which is based on the relationship of trust between society and institutionalized political parties. Political parties perform the role of mediators between social and political anxieties, which will be debated in the administrative sphere of the Brazilian State. It is true that the representativeness and efficiency of political parties in Brazil are questioned and other forms of democratic representation, such as independent candidates, appear as an alternative. However, these solutions start from arguments external to party democracy itself and try to resolve the issues with solutions that are also external to the Brazilian constitutional order. The weaknesses of the Brazilian democratic system can be corrected by reforming the representative system itself. Encouraging female participation, improving performance clauses, reducing the number of parties, optimizing punishment mechanisms in cases of party infidelity, and deconcentrating party decisions to local governing bodies are some of the internal measures to encourage democracy of the parties. This thesis supports the opposition of independent candidacies to Brazilian democracy, as enshrined in the 1988 Constitution and practiced in the discontinuous Brazilian democratic history. Therefore, it reviews the theory of democracy in Brazilian political parties to establish axiological and normative criteria that are specific and internal to the party system. Its objectives are to propose solutions to their weaknesses and refute parapartisan criteria, contrary to the constitutional text, such as the case of independent candidates.